Nexus between drinking patterns, gender and life satisfaction: Some evidence from Indigenous Australians. Issue 4 (15th March 2020) - Selvanathan, Eliyathamby A.; Selvanathan, Saroja; Jayasinghe, Maneka
Abstract: Excessive alcohol consumption results in a broad range of health problems and other social issues, such as violence, social disorder and family breakdown. As such, alcohol consumption is considered as a critical social policy issue in Australia. In this study, we have used ordered logit models to estimate the probability of an Indigenous person consuming alcohol and to assess the impact of alcohol consumption on self‐perceived life satisfaction. A heteroscedasticity‐corrected ordered logit model is used to identify the gender difference in such effects. For this purpose, we use the latest National Aboriginal and Torres Strait Islander Social Survey (NATSISS) 2014/2015 data collected by the Australian Bureau of Statistics. The estimation results reveal that age, gender, employment status, income and the experience of unfair treatments significantly affect Indigenous people's (level of) alcohol consumption. The results also reveal that any level of alcohol consumption is linked with reduced overall life satisfaction, which is another reason why prevention of alcohol misuse should be a priority. A significant gender differences in the medium‐risk‐level alcohol consumption were also observed. These findings could be used as an alcohol prevention message in developing and implementing alcohol prevention strategies and policies.